Predicting Year-End Financial Performance: Can Quarterly Earnings Be Used as an Indicator? - Chandra, Gregory Brendan; Kohardinata, Cliff (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
The main objective of this study is to analyze the ability of quarterly net income performance to make a prediction of year-end (Q4) net income growth in Indonesia’s banking sector. By adopting the adaptive expectations theory, this study examines the influence of net income growth in the first quarter (NIQ1), second quarter (NIQ2), and third quarter (NIQ3) on the fourth quarter (NIQ4). The data includes 57 banking companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2023. Multiple linear regression was implemented to conduct the analysis, and is also supported by several classical assumption tests, such as normality, heteroscedasticity, and multicollinearity tests. The outcomes demonstrate that both NIQ1 and NIQ3 have a significant positive impact on NIQ4, while NIQ2, by contrast, does not show a significant relationship. The findings of this research confirm that quarterly growth patterns of banks’ net income is able to be effectively estimated based on previous quarterly performances, particularly from Q1 and Q3. Thus, the findings provide broader insights for investors and company executives in making more informed decisions using available yet accountable historical information.